Twenty-year review of author characteristics and academic articles published in a medical student journal - Lorna Pairman; Angad S Chauhan (New Zealand Medical Student Journal)
All issues of the NZMSJ published prior to 2024 were retrospectively reviewed. Academic article characteristics and author demographics were described using counts and proportions. Characteristics were compared between the first and second decades of NZMSJ publication. For Issue 26 to Issue 36, journal metrics were also obtained. There were 144 academic articles published in the NZMSJ between 2004 and 2023. First authors tended to be medical students (74%), in their clinical years of medical school (56%), and from local universities (72%). There was a decline in the proportion of articles authored by preclinical students (from 25% to 6%) and with University of Otago affiliation (from (59% to 28%) when comparing the first and second decades of NZMSJ publication. Most articles had a single author (67%), were academic essays (38%), and were on a medical topic (58%). The median time between submission and acceptance was 3 months (IQR 2-6 months).